The emerging nanomedicine-based technology for non-small cell lung cancer immunotherapy: how far are we from an effective treatment - Peng, Lei; Xu, Quan; Yin, Sui; Zhang, Ye; Wu, Hao; Liu, Yangchun; Chen, Liru; Hu, Yeji; Yuan, Jun; Peng, Kai; Lin, Qin (Frontiers in Oncology, 2023)
The non-small cell lung cancer (NSCLC) keeps the leading common cause of cancer-associated mortality. The heterogeneous nature of this disease hinders its diagnosis and treatment, requiring continuous advances in research aiming to understand its intricate nature. Based on the conventional therapies, we have more chances to get the nanotechnology that can be considered to improve the clinical outcomes of NSCLC patients. Actually, the development of new emerging immunotherapies based on the recently understood interaction of the immune system with the tumor highlights some potential for treating NSCLC from the early stages. We believe with the new engineering avenues with nanomedicine, we will able to overcome the intrinsic limits of conventional and emerging therapies regarding off-site cytotoxicity, drug resistance and drug administration issues. The combination of nanotechnology to the convergence points of current therapies can pave the way for obtaining unmet needs for NSCLC treatment currently.